The Negotiation of Masculinities by Motorbike Taxi-Riders in Masaka, Uganda - Nyanzi, Stella; Nyanzi-Wakholi, Barbara; Kalina, Bessie (Men and Masculinities, 2009)
Understanding contemporary sociocultural constructions of masculinity and sexuality is crucial in the struggle against HIV/AIDS. This article discusses lay conceptualizations and enactments of manhood, in interaction with emic interpretations and practices of promiscuity. Data were collected from motorbike taxi-riders in southwest Uganda using ethnographic participant observation, a semi-structured questionnaire (n = 221), focus group discussions, in-depth interviews, case studies, and interactive workshops. Meanings and interpretations of masculinity are deeply imbued with sociocultural symbols drawn from the traditional, ritualistic, political, economic, and contemporary contexts. Social scripts and expectations are for males to engage in sexual activity as evidence of maturation. Higher social status, economic well-being, power, and “more manhood” are associated with multiple sexual partners. This male ideology perpetuates patriarchy and the commoditization of women, disparages messages of anti-HIV/AIDS campaigns, and supports risky sexual behavior. Sexual and reproductive health interventions should widen contemporary local perceptions and understandings of manhood to include safe sexual behavior
Keywords: masculinity; sexuality; Uganda; Africa; manhood; qualitative research; promiscuity